2021
DOI: 10.1049/rsn2.12087
|View full text |Cite
|
Sign up to set email alerts
|

Time reversal detection in a multistatic radar system with a varying environment

Abstract: Multistatic radar has the advantage of spatial diversity, but its detection performance is decreased in dense multipath scattering environments. This problem can be solved by using the time reversal (TR) technique to take advantage of the multipath effect to improve target detection; however, this usually requires a stationary channel response that is difficult to achieve in practice. This article studies a TR detection algorithm for a multistatic radar system in a varying multipath channel environment. We est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…The TR technique can combine various advantages, such as using multipath signals to build virtual sensors to expand the virtual radar aperture and adapting easily to other waveform design methods to improve target detection performance. Subsequently, TR technology is applied to target detection, leading to the development of various TR detectors that effectively enhance the detection performance for different radar systems [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The TR technique can combine various advantages, such as using multipath signals to build virtual sensors to expand the virtual radar aperture and adapting easily to other waveform design methods to improve target detection performance. Subsequently, TR technology is applied to target detection, leading to the development of various TR detectors that effectively enhance the detection performance for different radar systems [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the previous studies [18][19][20][21] on TR detection have primarily focused on ideal environments where no clutter is present or the target is assumed to be static. This continuous presence of clutter [23] and the dynamic nature of targets [24] significantly degrade the performance of radar detection systems.…”
Section: Introductionmentioning
confidence: 99%
“…The contributions of the proposed PolTR-GLRT detection include (1) combining the polarisation and TR to improve detection probability, (2) solving the problem of performance degradation of traditional TR detection caused by varying channels, (3) extending the limitations of traditional TR detection on statistical channel characteristics in [40][41][42][43].…”
Section: Introductionmentioning
confidence: 99%
“…Considering a varying channel, which is more realistic, the authors in [39] demonstrated the effectiveness of TR for non-stationary channels from information theory. The authors in [40][41][42][43] developed TR detectors specifically for a single antenna, the multiple-input-multiple-output radar and the multistatic radar under varying channel scenarios. Nevertheless, these detectors are applicable on the premise that the statistical characteristics of the channels remain unchanged, that is, the channels satisfy the complex Gaussian distribution, and the forward and backward channel variances are consistent.…”
Section: Introductionmentioning
confidence: 99%